Characteristics of Maintenance of Wakefulness Test (MWT) in drug-naïve patients with narcolepsy type 1 and type 2, and relationship with other measures of sleepiness - Biscarini, Francesco; Pizza, Fabio; Vandi, Stefano; Mazzoni, Alice; Barateau, Lucie; Mignot, Emmanuel; Dauvilliers, Yves; Plazzi, Giuseppe (Sleep (New York, N.Y.), 2025)
We aimed to describe the characteristics of standard maintenance of wakefulness test (MWT), outside of clinical trials, in a sample of drug-naïve patients with narcolepsy type 1 (NT1) and type 2 (NT2). Consecutive drug-naïve patients with narcolepsy underwent two days of continuous PSG recording, the multiple sleep latency test (MSLT), then night-PSG and, on the following day, MWT. MWT results were correlated with MSLT and Epworth Sleepiness Scale (ESS). Patients in the two lower tertiles of MWT mean sleep latency (mSL) were compared to those in the upper tertile. Seventy-eight NT1 (30.6 ± 11.4 years, 35 males) and 19 NT2 (31.0 ± 9.9 years, 12 males) were included. MWT results showed a bimodal distribution with a large peak with reduced mSL and a small peak with values towards 40 minutes. MWT mSL was lower in NT1 than in NT2 (10.7 ± 10.8 min vs 23.9 ± 11.5 min, p<.001). In the entire sample, lower MWT mSL was moderately correlated with lower MSLT mSL (Rho = 0.347, p=.001) and higher ESS (Rho = -0.398, p<.001). Patients with NT1 with MWT mSL in the two lower tertiles (≤11.2 min) had higher ESS than those in the upper tertile, without any difference in other clinical or neurophysiological features. In NT2, no significant correlations emerged between MWT, MSLT, and ESS. MWT mSL is reduced in drug-naive narcolepsy, more severely in NT1 than in NT2. However, a minority of patients show normal MWT results. MSLT, MWT, and ESS measure different aspects of sleepiness in narcolepsy, and none can be considered a comprehensive measure of its severity.